Association between Physical Activity and Sitting Time Related to Excess Body Weight in Brazilian University Students - Gerleison Ribeiro Barros; Sueyla Ferreira da Silva dos Santos; Alynne Christian Ribeiro Andaki; Thiago Ferreira de Sousa (Karger Publishers, 2023)
High exposure to sedentary behavior and lower levels of physical activity can lead to excess body weight (EBW). The aim of this study was to estimate the prevalence of EBW and the direct association under the condition of sociodemographic, university, and behavioral moderating characteristics, between physical activity and sitting time related to EBW in Brazilian university students. A cross-sectional study was carried out with 1,110 university students from a federal public institution in Minas Gerais, Brazil. The outcome was the EBW (body mass index: ≥25.0 kg/m2) and the independent variables were physical activity (insufficiently active and active) and sitting time (<6 h/day; ≥6 h/day). Association analyses were estimated via odds ratio (OR) using binary logistic regression. The significance level was 5%. The prevalence of EBW was 27.8%. No direct association was observed between physical activity and time sitting related to EBW. However, insufficiently active university students were more likely to have EBW (OR = 1.91; 95% CI: 1.06-3.47) when they did not consume alcoholic beverages, and university students with a sitting time of ≥6 h/day had lower chances of having EBW (OR = 0.62; 95% CI: 0.40-0.95) when they had spent more time at university (3 years or more). It is concluded that the prevalence of EBW in university students was high and there was no direct association between physical activity and sitting time; however, alcohol consumption and university time moderated the association with higher and lower chances of occurrence of EBW in university students, respectively.